Kaidah Fiqih Bila yang Halal Bercampur dengan yang Haram - Miftakhul Anwar (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2021)
This article discusses the kaidah fiqhiyyah / general rules of fiqh that explain the case "When something halal is mixed with something haram". The rules that are the subject of study are the rules that are raised by Imam Shafi'i in the book of Al-Umm, "every thing that is forbidden is mixed with what is lawful and cannot be distinguished/separated between the two, then everything is haram/unlawful." And a derivative of that rule. This article discusses the arguments for the rules, the meaning of the rules, examples of the rules and things that are excluded from the rules. In this study the data obtained through a literature review and processed using a descriptive-comparative method. This study aims to find the meaning of a fiqh rule and find out the origins / arguments and the extent of the scope of the rules discussed.